2012
DOI: 10.3109/10428194.2011.642303
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 expression is uniformly down-regulated in B cell lymphoproliferative disorders and is associated with poor survival in patients with chronic lymphocytic leukemia

Abstract: MicroRNA-223 (miR-223) expression has been demonstrated to be stage-specific in B cell differentiation and associated with the outcome of chronic lymphocytic leukemia (CLL). However, the expression pattern of miR-223 in B cell lymphoproliferative disorders and its association with the outcome of Chinese patients with CLL have not been investigated. In this study, we demonstrated that miR-223 expression was significantly decreased in CLL, mantle cell lymphoma (MCL) and splenic marginal zone lymphoma (SMZL). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
1
19
0
2
Order By: Relevance
“…Several of the miRNAs from this original signature could be confirmed, including increased expression of miR-15a 31,32 and miR-16 31 , and decreased expression of miR-29a 31 and miR-29b 33,34 as being associated with unmutated IGHV, and decreased levels of miR-29c 32,33,35,36 and miR-223 32,33,3537 as being associated with unmutated IGHV and with increased expression of ZAP70, CD38 and B2M. One miRNA that was not included in the original signature, but that was repeatedly reported to correlate with poor prognostic markers (unmutated IGHV and increased expression of ZAP70, CD38 and B2M) is miR-150.…”
Section: Mirnas Associated With Other Prognostic Factors In Cllmentioning
confidence: 84%
“…Several of the miRNAs from this original signature could be confirmed, including increased expression of miR-15a 31,32 and miR-16 31 , and decreased expression of miR-29a 31 and miR-29b 33,34 as being associated with unmutated IGHV, and decreased levels of miR-29c 32,33,35,36 and miR-223 32,33,3537 as being associated with unmutated IGHV and with increased expression of ZAP70, CD38 and B2M. One miRNA that was not included in the original signature, but that was repeatedly reported to correlate with poor prognostic markers (unmutated IGHV and increased expression of ZAP70, CD38 and B2M) is miR-150.…”
Section: Mirnas Associated With Other Prognostic Factors In Cllmentioning
confidence: 84%
“…There are, unfortunately, no studies of familial CLL in Asians. Most data suggest no important differences between Asians and persons of predominately European descent with CLL [103][104][105][106][107]. An exception is a study from Chim and colleagues who reported similar methylation of miR-9-2, a member of the miR-9 gene family, identified as tumor suppressor miRNA in normal CD19+ B-cells and CLL B-cells in Hong Kong Chinese.…”
Section: Geneticsmentioning
confidence: 85%
“…The literature search included 10 studies eligible in the meta-analysis (Figure 1), 6 from China13,17,18,21–23 and 1 each from France,24 United States,15 Japan,19 and Belgium 20. The studies involved a total of 1,002 patients with cancer, with mean sample size of 1,002 patients (range: 46–180).…”
Section: Resultsmentioning
confidence: 99%
“…MiR-223, a common tumor-associated microRNA, has been reported to be dysregulated in various human tumors, such as hepatocellular carcinoma,9 colorectal carcinoma,10 osteosarcoma,11 gastric cancer,12 and chronic lymphocytic leukemia 13. Abnormal expression of miR-223 in cancerous tissue has confirmed it as an important player in tumorigenesis of cancers 14.…”
Section: Introductionmentioning
confidence: 99%